VD_FINDINFO Décision / 2016 / 239 vom 11. April 2016 - VD Tribunal cantonal (2016)
MESURE DISCIPLINAIRE, DROIT CANTONAL, DÉTENU | 91 al. 3 CP, 38 al. 1 LEP, 38 al. 2 LEP, 38 LEP, 95 al. 1 LTF, 97 al. 1 LTF